Homeownership Among Millennials: The Deferred American Dream?. (December 2015) - Xu, Yilan; Johnson, Carrie; Bartholomae, Suzanne; O'Neill, Barbara; Gutter, Michael S.
Abstract : This article reviews external and internal factors influencing homeownership decisions for millennials, that is, those who were born between the 1980s and the early 2000s. The article was written by a multistate group of land‐grant university researchers to inform future research. The review of literature suggests that credit accessibility is an important external factor for millennials' homeownership. Also important are life cycle factors such as financial resources and student loans liabilities, and family decisions such as marriage and parenthood. It is anticipated that this information will enable financial advisors, educators, and policymakers to understand the challenges of homeownership for millennials and to formulate strategies to help this age cohort with their personal financial planning.